Caribbean Report 02-01-1995 - Crosskill, Hugh (anchor); Young, Janet Mary, Baroness (analyst); Baldry, Tony (interviewee); Bhola, Ronnie (correspondent); Graham, Ronald (interviewee); Douglas, Alexander (interviewee); Gilbert-Roberts, Marcia (interviewee) (The British Broadcasting Corporation, 1995)
This programme highlights the shift in British policy towards the Caribbean region in light of new global realities. Britain's Foreign Office Minister, Tony Baldry emphasizes the need for Britain to pay more attention to the Spanish-speaking countries in the region such as Puerto Rico, Cuba and the Dominican Republic. Anchor, Hugh Crosskill explores the issue of the British attitude towards the US trade embargo on Cuba. The report also looks at efforts made to encourage young black Britons to seek a new life in the Caribbean.
1. Headlines with Hugh Crosskill (00:00-00:39)
2. Report of the British shift in policy towards the Caribbean region (00:31-01:06)
3. Baroness Young declares that the British policy towards the Caribbean must change to reflect new global realities (01:17-01:59)
4. Hugh Crosskill interviews Tony Baldry (02:00-08:54)
Keywords: Caribbean Area -- Economic conditions -- 1945-; Cuba -- Foreign relations; Great Britain -- Economic policy; Great Britain -- Foreign relations -- Caribbean Area; Caribbean, English-speaking -- Foreign economic relations; Great Britain -- Commercial policy; Blacks -- Great Britain -- Emigration and immigration; Blacks -- Great Britain